Examining Women’s Agency, High Fertility and Maternal and Child Health in Tanzania (Tanzania Journal for Population studies and Development, 2016)
The paper considers why reproductive health has stalled in Tanzania. The individual woman in Tanzania gives birth to many children (TFR = 5.2). The demographic and economic transition is slow and the most striking characteristics is poor and lowlyeducated women having many children. The patterns of mortality among girls and women (and men) are still characterized by a predominance of infectious diseases. This makes women’s agency in bringing social and economic development so important. The argument is advanced that child-bearing will go down to replacement level and the wellbeing of women and children improve if women themselves become active agents of change or the dynamic promoters of social transformations that can alter their lives and the lives of children and men. The fundamental changes required to bring this in Tanzania is to put emphasis on the role of women’s agency. Some decline in infant and under-five mortality is observed in Tanzania, but it is argued that there is still much space for further decline in infant, under-five, and maternal mortality. It is further stated that there is much space to increase life expectancy by promoting active women’s agency.